Current Topics in Hypothyroidism with Focus on Development - Potluková, Eliška (IntechOpen, 2013)
Do you regard hypothyroidism as a more complex issue than just a simple prescription of levothyroxine tablet? Are you interested in getting more information on the management of thyroid dysfunction in pregnancy, at birth, in childhood or in subclinical states? Have you been thinking of performing thyroid ultrasound in hypothyroid patients by yourself, or perhaps you already do it and are not so sure about it? Than this book should give you some answers and help you form your own opinion. You will find there several excellent review articles from authors from all over the world.